Use of human aortic extracellular matrix as a scaffold for construction of a patient-specific tissue engineered vascular patch. (5th October 2017) - Gao, Li-Ping; Du, Ming-Jun; Lv, Jing-Jing; Schmull, Sebastian; Huang, Ri-Tai; Li, Jun
Abstract: Synthetic or biologic materials are usually used to repair vascular malformation in congenital heart defects; however, non-autologous materials show both mismatch compliance and antigenicity, as well as a lack of recellularization on its surface. Here, we constructed a tissue-engineered vascular patch (TEVP) using decellularized extracellular matrix (ECM) scaffold obtained from excised human aorta during surgery, which was seeded with patient-derived bone marrow CD34-positive (CD34+) progenitor cells. While cellular components were removed, the decellularized ECM scaffold retained native ECM composition, similar mechanical performance to undecellularized aortic tissue, and supported the adhesion, survival and proliferation of CD34+ progenitor cells. Interestingly, after in vitro seeding of decellularized aortic ECM scaffold for 21 d, CD34+ progenitor cells differentiated into mature vascular endothelial cells without addition of any growth factors, as confirmed by the increased levels of endothelial surface markers (CD31, Von Willebrand factor (VWF), VE-cadherin and ICAM-2) and upregulated gene levels (CD31, VWF and eNOS) concurrently with decreased expression of stem cell markers (CD133 and CD34), thus, resulting in surface endothelialization of decellularized ECM scaffold. Consequently, the patient-specific TEVP constructed in this study holds great potential for clinical use in pediatric patients with vascular malformation.